Effect of pyrolysis temperature on physicochemical properties of biochars made from two different bamboo species - Maia, Claudia Maria Branco de Freitas; Baratto, Ricardo Luis; Guiotoku, Marcela; Siqueira, Franciely Cristina de Jesus; Madari, Beata Emoke; Leal, Wesley Gabriel de Oliveira (Seven Editora, 2023)
Due to its high photosynthetic efficiency and conversion into biomass, bamboo has great potential for the production of coal for agricultural use (biochar). This work compared  the coals produced at different pyrolysis temperatures from the stem of two  species of wide occurrence in the south of the country: Phyllostachys aurea (an exotic species) and Guadua sp. (southern Brazil). The results showed differences between the two species, starting with the lignin and volatile content of the stems in natura,  and the exotic species showed higher levels of lignin and lower levels of extractives. These differences are reflected in the pyrolysis process and in the chemical characteristics of the coals, and the exotic species produces coals with higher carbon contents. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-010